Replacing Part of Glucose with Galactose in the Postweaning Diet Protects Female But Not Male Mice from High-Fat Diet–Induced Adiposity in Later Life - Bouwman, Lianne M S (J Nutr, 2019)
BACKGROUND: Duration of breastfeeding is positively associated with decreased adiposity and increased metabolic health in later life, which might be related to galactose. OBJECTIVE: The aim of this study was to investigate if partial replacement of glucose with galactose in the postweaning diet had a metabolic programming effect. METHODS: Male and female mice (C57BL/6JRccHsd) received an isocaloric diet (16 energy% fat; 64 energy% carbohydrates; 20 energy% protein) with either glucose (32 energy%) (GLU) or glucose + galactose (GLU + GAL, 16 energy% each) for 3 wk postweaning. Afterwards, all mice were switched to the same 40 energy% high-fat diet (HFD) for 9 wk to evaluate potential programming effects in an obesogenic environment. Data were analyzed within sex. RESULTS: Female body weight (−14%) and fat mass (−47%) were significantly lower at the end of the HFD period (both P < 0.001) among those fed GLU + GAL than among those fed GLU; effects in males were in line with these findings but nonsignificant. Food intake was affected in GLU + GAL–fed females (+8% on postweaning diet, −9% on HFD) compared with GLU-fed females, but not for hypothalamic transcript levels at endpoint. Also, in GLU + GAL–fed females, serum insulin concentrations (−48%, P  < 0.05) and the associated homeostasis model assessment of insulin resistance (HOMA-IR) were significantly lower ( P < 0.05) at endpoint, but there were no changes in pancreas morphology. In GLU + GAL–fed females, expression of insulin receptor substrate 2 (Irs2) (−27%, P  < 0.01 ; −44%, P  < 0.001) and the adipocyte size markers leptin (Lep) (−40%, P  < 0.05; −63% , P  < 0.05) and mesoderm-specific transcript homolog protein (Mest) (−80%, P < 0.05; −72%, P  < 0.05) was lower in gonadal and subcutaneous white adipose tissue (WAT), respectively. Expression of insulin receptor substrate1 (Irs1) (−24%, P  < 0.05) was only lower in subcutaneous WAT in GLU + GAL–fed females. CONCLUSIONS: Partial replacement of glucose with galactose, resulting in a 1:1 ratio mimicking lactose, in a 3-wk postweaning diet lowered body weight, adiposity, HOMA-IR, and expression of WAT insulin signaling in HFD-challenged female mice in later life. This suggests that prolonged galactose intake may improve metabolic and overall health in later life.